Le fracas du soleil ou Jean-Baptiste Lully le musicien du roi - David, Marc 1948- (Paris Perrin, 2000)
Jean-Baptiste Lully was twenty and the King fifteen when they met for the first time in 1653, during the Ballet de la Nuit. Louis XIV danced in his sun dress. It was daybreak, the dawn of a reign. It takes place shortly after the presentation to the court of fourteen-year-old Marie Mancini, Mazarin's niece. Listening to this young girl perform Le Cid in a moving way, the king falls in love. Marie, Louis and Jean-Baptiste became one, and the forest of Fontainebleau echoed with their wild cavalcades in the summer of 1658. Witty and literate, Marie recounts Persée, Armide and many other legends that Lully sublimates with the strokes of his violin. But love will have to give way to the raison d'état and the beautiful Mancini will have to resign herself to leaving for Rome to marry the Constable Colonna. Yet the legends remain, and Lully has not forgotten the voice that now haunts him. Like Armide using her enchantments, Marie would be his muse and magician throughout his life, leading him to create French opera based on her fabulous tales. Among them, the myth of Phaeton, the son of the Sun who claims to drive the luminous chariot to the zenith and ends up smashed, inspired Lully, whose life would meet the same kind of fate. Along with the character of Marie Mancini, it is one of the main threads running through this romanticised life of the King's music superintendent and director of the Royal Academy of Music. (Translated with Deepl.com)
Keywords: Lully, Jean-Baptiste -- 1632-1687; 17th Century (1601-1700); Music history; Versailles (France)